Humans and seasonal climate variability threaten large-bodied coral reef fish with small ranges - C. Mellin (Nature Portfolio, 2016)
Knowing which species traits may confer resilience to human-mediated stressors will help predict future impacts on biodiversity. Here, Mellin et al. show that large bodied fish with small geographic ranges are disproportionately affected by the negative impacts of human disturbance and climate variability.